Genome-wide analysis of MADS-box gene family in kiwifruit (Actinidia chinensis var. chinensis) and their potential role in floral sex differentiation - Ye, Li-Xia; Luo, Min-Min; Wang, Zhi; Bai, Fu-Xi; Luo, Xuan; Gao, Lei; Peng, Jue; Chen, Qing-Hong; Zhang, Lei (Frontiers in Genetics, 2022)
Kiwifruit (Actinidia chinensis Planch.) is a functionally dioecious plant, which displays diverse morphology in male and female flowers. MADS-box is an ancient and huge gene family that plays a key role in plant floral organ differentiation. In this study, we have identified 89 MADS-box genes from A. chinensis Red 5 genome. These genes are distributed on 26 chromosomes and are classified into type I (21 genes) and type II (68 genes). Overall, type II AcMADS-box genes have more complex structures than type I with more exons, protein domains, and motifs, indicating that type II genes may have more diverse functions. Gene duplication analysis showed that most collinearity occurred in type II AcMADS-box genes, which was consistent with a large number of type II genes. Analysis of cis-acting elements in promoters showed that AcMADS-box genes are mainly associated with light and phytohormone responsiveness. The expression profile of AcMADS-box genes in different tissues showed that most genes were highly expressed in flowers. Further, the qRT-PCR analysis of the floral organ ABCDE model-related genes in male and female flowers revealed that AcMADS4, AcMADS56, and AcMADS70 were significantly expressed in female flowers. It indicated that those genes may play an important role in the sex differentiation of kiwifruit. This work provided a comprehensive analysis of the AcMADS-box genes and may help facilitate our understanding of the sex differentiation regulatory mechanism in kiwifruit.